2005
DOI: 10.1073/pnas.0501424102
|View full text |Cite
|
Sign up to set email alerts
|

Patellamide A and C biosynthesis by a microcin-like pathway inProchloron didemni, the cyanobacterial symbiont ofLissoclinum patella

Abstract: Prochloron spp. are obligate cyanobacterial symbionts of many didemnid family ascidians. It has been proposed that the cyclic peptides of the patellamide class found in didemnid extracts are synthesized by Prochloron spp., but studies in which host and symbiont cells are separated and chemically analyzed to identify the biosynthetic source have yielded inconclusive results. As part of the Prochloron didemni sequencing project, we identified patellamide biosynthetic genes and confirmed their function by heterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
717
1
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 552 publications
(736 citation statements)
references
References 50 publications
(49 reference statements)
11
717
1
5
Order By: Relevance
“…Repeating essentially the autoannotation of Schmidt et al, 6 a search of the whole Pfam HMM library with each protein sequence of seven Prochloron didemni genes did not show the presence of additional adenylation, epimerisation, racemisation or cyclisation domains other than those shown in the sequence description. The highest scores and most relevant results were obtained with peptidase S8 from the subtilase family found in patA subtilisin-like protein and as a part of patG thiazoline oxidase/subtilisin-like protease and the YcaO from YcaO-like family found in the patD adenylation/heterocyclisation protein (identified by match to protein families HMM PF00082 and HMM PF02624).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Repeating essentially the autoannotation of Schmidt et al, 6 a search of the whole Pfam HMM library with each protein sequence of seven Prochloron didemni genes did not show the presence of additional adenylation, epimerisation, racemisation or cyclisation domains other than those shown in the sequence description. The highest scores and most relevant results were obtained with peptidase S8 from the subtilase family found in patA subtilisin-like protein and as a part of patG thiazoline oxidase/subtilisin-like protease and the YcaO from YcaO-like family found in the patD adenylation/heterocyclisation protein (identified by match to protein families HMM PF00082 and HMM PF02624).…”
Section: Resultsmentioning
confidence: 91%
“…4 L. patella contains an as yet uncultured primitive photosynthetic prokaryote Prochloron didemni, which is closely related to the cyanobacteria, but differs in the fact that it possesses both chlorophylls a and b, lacks phycobilins and has plant-like thylakoids. 5 Recent work has indicated that the patellamides are unprecedented examples of post-translationally modified ribosomal peptides, 6 produced by the Prochloron didemni symbiont. 7 The patellamides are the most complex examples of this unusual family of peptides which includes the lantibiotics 8 and microcins, 4 as they contain a unique combination of heterocycles (cf microcin B17), 4 a macrocycle (cf microcin J25) 9 and D stereocentres.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though most bacteria are not readily cultured in the laboratory, it is possible to extract microbial DNA directly from the naturally occurring consortia of bacteria present in environmental samples (environmental DNA (eDNA)). Introduction of this previously inaccessible genetic material into easily cultured bacterial hosts provides one means to access the biosynthetic potential of uncultured bacteria [3][4][5][6][7][8][9][10][11][12][13] . Culture-independent analysis of the genetic and biochemical diversity present in naturally occurring bacterial communities, which began in the 1990s (see refs.…”
Section: Introductionmentioning
confidence: 99%
“…However, only two examples employing this strategy exist, one involving marine animals, 4 and the other the uncultivated human microbiota, 5,6 leaving substantial hurdles to accessing chemical novelty. Collectively, such systems feature hundreds or thousands of biosynthetic pathways to bioactive compounds, only a few of which have been accessed.…”
Section: Introductionmentioning
confidence: 99%